Multi-band patch antenna for GNSS - Siddhant, Sahoo (2016)
A multi-band stack patch antennas for Global Navigation Satellite System (GNSS) applications has been designed and studied. The antenna designed consists of two square patches in a stack configuration. The patch corners are chirped in order to enhance the circular polarisation for both the bands and improve the radiation pattern. The structure contains a single feed patch antenna which is designed using the Rogers R04003 substrate. This antenna was designed using a single feed which reduces the cost of antenna. The proposed antenna is structured using the High frequency Structure Simulator (HFSS).A parametric analysis is done using the optimisation tool box in HFSS to achieve higher performance. The objective of this thesis is to analyse and design a stacked microstrip square patch antenna that works in all the GNSS frequency bands. The predicted 10 dB return loss bandwidth can be observed to be around 32.7 MHz for the lower band and 40 MHz for the higher band. The return loss noted at the lowest point for lower band was around -22.49 dB at 1.26 GHz and -28.12 dB at 1.6064 GHz.The highest value of the realized gain for the lower band at 1.2691 GHz is noted to be around 3.84 dBic and for the higher band at 1.61 GHz is noted to be around 5.98 dBic.The bandwidth observed along the 3dB axial ratio is 7.5 MHz for lower band and 8.8 MHz for upper band. In conclusion, a stacked microstrip square patch microstrip antenna with truncated corners was designed and studied. The antenna has fulfilled the design specifications suitable for applications in GNSS antennas used in L1 and L2 bands.